Understanding the Epidemiology of Multi-Drug Resistant Gram-Negative Bacilli in the Middle East Using a One Health Approach - Dandachi, Iman; Chaddad, Amer; Hanna, Jason; Matta, Jessika; Daoud, Ziad (Frontiers in Microbiology, 2019)
In the last decade, extended-spectrum cephalosporin and carbapenem resistant Gram-negative bacilli have been extensively reported in the literature as being disseminated in humans but also in animals and the environment. These resistant organisms often cause treatment challenges due to their wide spectrum of antibiotic resistance. With the emergence of colistin resistance in animals and its subsequent detection in humans, the situation was worsened. Several studies reported the transmission of resistant organisms from animals to humans. Studies from the middle east highlighted the spread of resistant organisms in hospitals and to a lesser extent in livestock and the environment. In view of the recent socio-economical conflicts that these countries are facing in addition to the constant population mobilization; we attempt in this review to highlight the gaps as for the prevalence of resistance, antibiotic consumption reports, infection control measures and other risk factors contributing in particular to the spread of resistance in these countries. In hospitals, carbapenemase producers appear to be dominant. In contrast, ESBLs and colistin resistance are becoming a serious problem in animals. This is mainly due to the continuous use of colistin in veterinary medicine although it was previously abandoned in the human sphere. In the environment, despite the small number of reports, ESBL and carbapenemase producers were both detected. This highlights the importance of this latter as a bridge between humans and animals in the transmission chain. In this review, we have noticed that in the majority of the Middle Eastern area, little is known about the level of antibiotic consumption especially in the community and animal farms. Furthermore, some countries are nowadays facing the burden of immigrants, poverty and poor living conditions imposed by the civil war crisis. This all facilitates more the dissemination of resistance in all environments. In the one health concept, this work re-emphasizes the need to have global intervention measures to avoid dissemination of antibiotic resistance in humans, animals and environment in Middle Eastern countries.